London Dock Strike - Finance Committee, 1889 (1889)
1889 1880-1914 "London Dock Strike - Finance Committee, 1889" [T0021.jpg], 1889 This drawing of the Committee meeting at Wade's Arms public house in Jeremiah Street, Poplar includes John Burns, Tom Mann and Ben Tillett. Donations to the Strike Fund amounted to £48,736, including £30,000 collected in Australia. To avoid abuses no cash was paid to strikers, but with the help of East End shopkeepers, thousands of food tickets were distributed daily. At the peak of the strike, 100,000 workers were involved, including every class of waterfront labour.